The effect of antiarrhythmic medications on the risk of cardiovascular outcomes in patients with atrial fibrillation and coronary artery disease - Wang, Shih-Rong; Huang, Kuan-Chih; Lin, Ting-Tse; Chuang, Shu-Lin; Yang, Yen-Yun; Wu, Cho-Kai; Lin, Lian-Yu (International journal of cardiology, 2024)
While current guidelines recommend amiodarone and dronedarone for rhythm control in patients with atrial fibrillation (AF) and coronary artery disease (CAD), there was no comparative study of antiarrhythmic drugs (AADs) on the cardiovascular outcomes in general practice. This study included patients with AF and CAD who received their first prescription of amiodarone, class Ic AADs (flecainide, propafenone), dronedarone or sotalol between January 2016 and December 2020. The primary outcome was a composite of hospitalization for heart failure (HHF), stroke, acute myocardial infarction (AMI), and cardiovascular death. We used Cox proportional regression models, including with inverse probability of treatment weighting (IPTW), to estimate the relationship between AADs and cardiovascular outcomes. Among the AF cohort consisting of 8752 patients, 1996 individuals had CAD, including 477 who took dronedarone and 1519 who took other AADs. After a median follow-up of 38 months, 46.3% of patients who took dronedarone and 54.4% of patients who took other AADs experienced cardiovascular events. Compared to dronedarone, the use of other AADs was associated with increased cardiovascular events after adjusting for covariates (hazard ratio [HR] 1.531, 95% confidence interval [CI] 1.112–2.141, p = 0.023) and IPTW (HR 1.491, 95% CI 1.174–1.992, p = 0.012). The secondary analysis showed that amiodarone and class Ic drugs were associated with an increased risk of HHF. The low number of subjects in the sotalol group limits data interpretation. For patients with AF and CAD, dronedarone was associated with better cardiovascular outcomes than other AADs. Amiodarone and class Ic AADs were associated with a higher risk of cardiovascular events, particularly HHF. [Display omitted] •In this study cohort in Taiwan, 53.5% of patients with AF and CAD took amiodarone as first-line AAD, 23.9% took dronedarone, 19.7% took class Ic drugs and 2.9% took sotalol.•For patients with AF and CAD, dronedarone was associated with better cardiovascular outcomes than other AADs.•Amiodarone and class Ic AADs were associated with a higher risk of cardiovascular events, particularly hospitalization for heart failure (HHF).•Our study suggested that dronedarone is the preferred first-line choice for rhythm control in patients with AF and CAD.